The Economic Impact of Mobile Broadband Speed - Harald Edquist (International Telecommunications Society (ITS), 2021)
Based on panel data of 116 countries in 2014-2019, this paper investigates the association between mobile broadband speed and labor productivity. It finds no robust contemporaneous relationship, but there is a significant and robust effect when a one-year lag of mobile broadband speed is introduced (significant at 3.7 and 0.9 percent levels for fixed and random effects estimation, respectively). The interpretation of the results is that a 10 percent increase in mobile broadband speed in period t-1 is associated with 0.2 percent increase in labor productivity, cetris paribus.
Keywords: 330